Amino Acid Sequence Database Suitable for the Protein and Proteome Analysis - Kawakami, Takao; Ozaki, Junko; Kondo, Kazuhiro; Sato, Shinji; Yunokawa, Harunobu (Current Proteomics, 2008)
Amino acid sequence database is one of the essential components in the current proteomics with mass spectrometry. Protein identification routine as well as posttranslational modification analysis is based on correlation between the mass spectrometry data of peptides obtained from proteome and the entry sequences in the database. While different sequence databases are available from public resources for the correlation search, these primary sequence data can be processed into more useful forms. In alteration of the unmodified precursor sequences according to their biological processes and variations, the altered sequence database allows to output the search results on the matured polypeptides. Modification of the composition in sequence database would be practically beneficial to the wide range from the detail analysis focusing on a single protein to the biomarker discovery studies for the clinical utility.
Keywords: tandem mass spectrometry